PENGARUH PELATIHAN TERHADAP KEMAMPUAN KADER DALAM MELAKUKAN DETEKSI DINI STROKE PRA – RUMAH SAKIT - Irine Yunila Prastyawati; Dominggus Ruku Yudit Pramono; Ignata Yuliati (Jurnal Keperawatan Malang, 2024)
Background: Pre-hospital stroke management has been suboptimal, leading to delays from symptom onset to treatment administration in stroke patients. Improving pre-hospital care can be achieved by training community health workers (cadres).Purpose: To determine the impact of training on the skills of cadres in performing early stroke detection before hospitalization. Methods: This study employed a pre-experimental design with a one-group pretest-posttest design. The sample consisted of cadres from Gisikcemandi Village who met the inclusion criteria: 1) willing to participate as respondents, and 2) actively serving as cadres. The sampling technique used was purposive sampling, resulting in 30 respondents. The intervention was training on early stroke detection before hospitalization, with the cadres' skills in early stroke detection measured. Data were analyzed using SPSS with the Wilcoxon testResult: The average age of respondents was 43.37 years (SD±6.8). Before the training, the majority, 83% (25) of respondents, had basic practical skills, and 17% (5) had guided practical skills. After the training on early stroke detection, the respondents' skills improved to 63,34% (19) with adoption-level skills, 33,33% (10) with basic practical skills, and 3,3% (1) with guided practical skills. The results showed a Z-score of -4.796 with a p-value of 0.000 < 0.05, indicating a significant difference before and after the early stroke detection training for the cadres.Implication: The training had a significant impact on the skills of cadres in performing early stroke detection before hospitalization. Continuous training and evaluation of the effectiveness of early stroke detection training are necessary for long-term success